Women’s Morals or Customary Panopticism? Re-examining the Sumbang Duo Baleh in Minangkabau, West Sumatra, Indonesia - Sulistyati, Mardian (JSW (Jurnal Sosiologi Walisongo), 2024)
The shariatization of customs and regional regulations on women form an interdependence between morality, sexuality, and the nation. Currently, there are at least fifteen Shari’a regulations in West Sumatra that target women's bodies and expressions. This study employs a reflective approach, drawing from personal experience in the Minangkabau context, and critically examines the concept of sumbang duo baleh—a set of twelve female characteristics deemed inappropriate according to custom. Aiming to trace the roots of these regional regulations or Shari’a policies in West Sumatra, especially those regulating women's activity and expression, the analysis focuses on three key issues: First, custom-discursiveness and shariatization of the body and morals of Minang women nowadays. Second, the portrait of women in the sumbang duo baleh, critical factors, and how women’s characters are projected into custom ideals. Third, moral construction through the gaze mechanism and its implementation in the Shari’a regulations. This systematic analysis reveals underlying gender injustice in the way individuals are positioned within the framework of sumbang duo baleh.__________The original draft of this article has been presented at the 23rd Annual International Conference on Islamic Studies (AICIS), February 1-4, 2024 at Universitas Islam Negeri Walisongo Semarang, Indonesia.